A high heat-resistant, high-strength, multi-layer co-extruded high-barrier film, preparation method and application

By adopting a seven-layer structure and a modified polyethylene layer design in the multi-layer coextruded high-barrier film, the shortcomings of existing film materials in terms of heat resistance and strength are solved, and higher heat resistance, mechanical strength and barrier properties are achieved.

CN119078325BActive Publication Date: 2025-03-28CHONGQING MEICHEN NEW MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411297789.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-03-28
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing multi-layer coextruded high-barrier membranes have shortcomings in heat resistance and strength performance, and it is difficult to maintain performance under high temperature environments and mechanical stresses.

Method used

A multi-layer coextruded high-barrier membrane with a seven-layer structure is adopted, including a modified polyethylene layer, an adhesive resin layer, a polyamide composite layer, an ethylene-vinyl alcohol copolymer composite layer, etc., through reasonable composition distribution ratio and preparation process, synergistic effects between each layer are achieved.

Benefits of technology

The heat resistance, mechanical strength and barrier properties of the film are significantly improved, ensuring that good performance can be maintained under high temperature and mechanical stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119078325B_ABST
    Figure CN119078325B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of composite packaging films, and provides a high-heat-resistant and high-strength multi-layer co-extruded high-barrier film, a preparation method and its application. The film consists of seven layers, including a modified polyethylene layer, an adhesive resin layer, a polyamide composite layer and an ethylene-vinyl alcohol copolymer composite layer; the film innovatively integrates a modified polyethylene layer, and cleverly adds carboxyl functionalized graphene and polyethylene, which significantly improves thermal stability and mechanical strength. The polyamide composite layer is strengthened by surface-modified boron nitride nanosheets to improve the barrier performance; the ethylene-vinyl alcohol copolymer layer has improved performance due to the modification of microcrystalline cellulose. The preparation method includes the steps of mixing raw materials, plasticizing and extruding, blow molding, cooling and shaping, and traction and winding. The present invention adopts a multi-layer co-extrusion structure design to achieve excellent heat resistance, mechanical strength and barrier performance, solves the problem of insufficient performance of traditional single-layer films, and has wide application value in the fields of food packaging, medical packaging, and new energy battery packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite packaging films, and in particular to a high-heat-resistant, high-strength, multi-layer co-extruded high-barrier film, a preparation method and application thereof. Background Art

[0002] With the rapid development of the food packaging and medical device industries, the demand for high-performance packaging materials is growing. As a key functional material, high-barrier films play a vital role in maintaining the freshness of food, extending the shelf life of drugs, and protecting sensitive medical devices. However, existing barrier films often find it difficult to simultaneously achieve high heat resistance and high strength when faced with challenges such as high-temperature sterilization, long-term storage, and mechanical stress during transportation. Improving the heat resistance of barrier films can significantly expand their application range in high-temperature sterilization and thermal packaging, while enhancing their mechanical strength can improve the integrity and reliability of packaging and reduce the risk of damage during production, transportation, and use. Therefore, developing a multi-layer co-extruded high-barrier film with both high heat resistance and high strength can not only meet the increasingly stringent packaging requirements of the food and medical industries, but also promote the innovation of packaging technology and provide strong support for improving product quality and safety.

[0003] At present, the research and application of high barrier films still face many challenges and shortcomings. In the prior art, it is often difficult to achieve both high heat resistance and high strength, mainly because the microstructure of the material may sacrifice another property when improving one property. For example, increasing the degree of crystallinity can improve heat resistance, but it may cause the material to become brittle and reduce strength. In addition, although the multi-layer structure design can combine the advantages of different materials, the combination optimization between the layers still restricts the further improvement of performance. For example, the Chinese patent with publication number CN105778208A discloses a multi-layer co-extruded barrier film, but there are problems with insufficient heat resistance and strength, which is difficult to meet the requirements of more demanding environments. On the other hand, although some high-strength barrier films have excellent mechanical properties, they are prone to deformation or structural damage in high temperature environments, which limits their scope of application. Therefore, the development of a new multi-layer co-extruded high-barrier film that can synergistically optimize heat resistance and strength at the molecular and structural levels has become the focus and difficulty of current research. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a high-heat-resistant and high-strength multi-layer co-extruded high-barrier film, a preparation method and an application thereof, so as to solve the problem that the current multi-layer co-extruded high-barrier film has insufficient heat resistance and strength performance.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A high heat-resistant and high-strength multi-layer co-extruded high-barrier film, comprising seven mutually contacting films, which are, in order, a first modified polyethylene layer, a first adhesive resin layer, a first polyamide composite layer, an ethylene-vinyl alcohol copolymer composite layer, a second adhesive resin layer, a second polyamide composite layer and a second modified polyethylene layer;

[0009] The first modified polyethylene layer or the second modified polyethylene layer is prepared from the following components by weight: 2 parts of carboxyl functionalized graphene, 0.8-1.5 parts of epoxidized soybean oil, 40-60 parts of carboxyl functionalized polyethylene and 0.5-1 part of sodium dodecylbenzene sulfonate.

[0010] The first polyamide composite layer or the second polyamide composite layer is prepared from the following components by weight: 3.0-6.0 parts of surface modified layered hexagonal boron nitride nanosheets, 0.3-0.6 parts of erucic acid amide and 60-80 parts of polyamide mixed powder.

[0011] The ethylene-vinyl alcohol copolymer composite layer is prepared from the following components by weight: 100 parts of ethylene-vinyl alcohol copolymer, 2.0-4.5 parts of surface-modified microcrystalline cellulose and 0.3-0.8 parts of polyethylene wax.

[0012] Furthermore, the mass ratio of the carboxyl functionalized graphene to the carboxyl functionalized polyethylene is 1:(20-30).

[0013] Furthermore, the preparation method of the carboxyl functionalized polyethylene is as follows: in parts by weight, 100 parts of mixed polyethylene, 300-500 parts of xylene and 0.1-0.5 parts of diisopropylbenzene peroxide are mixed evenly, and then 5-15 parts of acrylic acid are added, and the mixture is heated to 120-150°C under a nitrogen atmosphere, and then stirred for reaction for 120-240 minutes. After the reaction is completed, the cooled reaction solution is slowly injected into 200 parts of methanol in a dropwise manner. At this time, the target product can be observed to precipitate as a white flocculent precipitate, and then the obtained precipitated product is collected by vacuum filtration separation technology, and the precipitated product is washed 3 times with methanol. Finally, the wet precipitated product is placed in a vacuum drying device and dried at 50-60°C for 12-24 hours to constant weight to obtain the desired carboxyl functionalized polyethylene.

[0014] Furthermore, the mixed polyethylene is composed of low-density polyethylene and linear low-density polyethylene in a mass ratio of (4-6):(6-4).

[0015] Further, the preparation method of the carboxyl functionalized graphene is as follows: first, 5 to 10 parts of graphene oxide are added to 200 parts of deionized water at 150 °C. W power for 120-240 min to form a colloidal dispersion, then, 40 parts of hydrazine hydrate are slowly added to the dispersion, the reaction mixture is stirred under reflux conditions for 6-12 h, and then the precipitated product is collected by filtration, and then the precipitated product is washed with deionized water for 3 times, and then dried in a vacuum drying oven at 50-65 ° C to constant weight to obtain chemically reduced graphene oxide; next, 6-12 parts of chemically reduced graphene oxide and 200 parts of toluene are mixed evenly, and then 20-28 parts of azobisisobutyronitrile are added, and vigorously stirred at 70-80 ° C for 240 min under an argon atmosphere, and then the solution is cooled to room temperature and the solution is filtered to collect the precipitate, and the precipitate is washed with toluene 3 times, and then the wet precipitated product is placed in a vacuum drying device to obtain cyano-modified chemically reduced graphene oxide at room temperature to constant weight; then, 10-16 parts of cyano-modified chemically reduced graphene oxide are dispersed in 100 parts of methanol, and 100 parts of 10 mol / L sodium hydroxide aqueous solution, reflux and stir at 55-65°C for 10-20h, then filter the reaction mixture to collect the precipitated product, wash the precipitated product with deionized water 3 times, then wash it with 1mol / L hydrochloric acid three times, and continue to wash it with a large amount of deionized water until it is neutral. Finally, dry the obtained solid in a vacuum drying oven at 50°C to constant weight to obtain the target product, carboxyl functionalized graphene.

[0016] The present invention adopts the design of the first modified polyethylene, and the carboxyl functionalized polyethylene is modified by introducing carboxyl functionalized graphene to form the first modified polyethylene, thereby achieving a comprehensive improvement in heat resistance, high strength and barrier performance of the high barrier film. In the preparation process, a mixture of low-density polyethylene and linear low-density polyethylene is selected as a raw material, and their complementary effects in mechanical properties, processing properties, etc. are utilized to obtain a matrix material with excellent comprehensive performance. Acrylic acid is grafted onto the mixed polyethylene through a free radical grafting reaction, and a large number of hydrophilic carboxyl groups are introduced, which significantly improves the polarity and reactivity of the material, and provides a favorable chemical basis for subsequent graphene composite and functional modification. In the preparation and modification process of graphene, chemical reduction of graphene oxide improves its dispersibility, and a carboxyl functionalized graphene with good hydrophilicity is obtained through coupling agent cyanation and hydrolysis reaction, which not only fully restores the conjugated structure of graphene, but also introduces a large number of functional groups on its surface that are conducive to dispersion and interface bonding. Epoxidized soybean oil plays multiple roles in the present invention. First, as a natural and environmentally friendly dispersant, it can effectively promote the uniform dispersion of carboxyl functionalized graphene in the polyethylene matrix, prevent the agglomeration of graphene sheets, and give full play to its reinforcing effect. Sodium dodecylbenzene sulfonate is used as a dispersant to further improve the dispersibility of graphene sheets. The synergistic effect between these multiple components not only improves the barrier properties of the film, but also enhances its mechanical strength and heat resistance. In terms of barrier properties, the lamellar structure of carboxyl functionalized graphene forms a circuitous diffusion path, which effectively prevents the penetration of gas molecules. At the same time, the hydrogen bond network that may be formed between carboxyl functionalized polyethylene and graphene further enhances the barrier effect. In terms of mechanical properties, the high strength characteristics of graphene are combined with the flexibility of the polyethylene matrix to achieve a balance between strength and toughness. The improvement in heat resistance comes from the excellent thermal stability of graphene and the cross-linked network structure that may be formed. By accurately controlling the ratio of each component, especially the amount of epoxy soybean oil, the performance of the film can be flexibly adjusted to meet the needs of different application scenarios. This multi-component collaborative design concept not only achieves a comprehensive improvement in the performance of high-barrier films, but also provides innovative ideas for the development of new functional materials.

[0017] Furthermore, the polyamide mixed powder is prepared by mixing polyamide 66 and polyamide 6 in a mass ratio of (6-4): (4-6).

[0018] Furthermore, the preparation method of the surface modified layered hexagonal boron nitride nanosheets is as follows: by weight, 2 to 6 parts of layered hexagonal boron nitride nanosheets and 50 to 100 parts of anhydrous ethanol are mixed, and ultrasonic dispersion is performed for 30 to 60 minutes to obtain solution A; then 1.0 to 3.0 parts of 3-aminopropyltriethoxysilane are dissolved in 50 to 100 parts of anhydrous ethanol, and stirred evenly to obtain solution B; solution B is slowly added dropwise to solution A, and refluxed at 60 to 80° C. for 4 to 8 hours; after the reaction is completed, the solid powder is collected by centrifugation, and then the solid powder is washed twice with anhydrous ethanol, and finally the wet solid powder is dried in a vacuum drying oven at 40 to 60° C. for 12 to 24 hours to obtain surface modified layered hexagonal boron nitride nanosheets.

[0019] The present invention adopts the design of the first polyamide layer mainly to enhance the heat resistance, high strength and barrier properties of the high barrier film. This technical solution achieves a synergistic improvement in multiple performances by cleverly combining the excellent properties of surface-modified layered hexagonal boron nitride nanosheets and polyamide mixed powders. In this innovative design, the surface-modified layered hexagonal boron nitride nanosheets plays a key enhancement role. Hexagonal boron nitride provides excellent heat resistance and mechanical strength for the film due to its unique layered structure and excellent physical and chemical properties. Through surface modification, not only the compatibility of hexagonal boron nitride nanosheets with the polyamide matrix is ​​improved, but also the interfacial bonding force is enhanced, thereby more effectively exerting its enhancement effect. Erucic acid amide can help improve the dispersibility of nanosheets in the polyamide matrix and prevent nanoparticles from agglomerating. In addition, it can improve the interfacial compatibility between surface-modified layered hexagonal boron nitride nanosheets and the polyamide matrix. This modification strategy helps to form a stable composite system, prevent the agglomeration of nanosheets in the matrix, ensure their uniform dispersion, and give full play to the nanoscale effect. As a matrix material, polyamide mixed powder itself has excellent heat resistance and mechanical strength. These properties are further enhanced by compounding with surface-modified hexagonal boron nitride nanosheets. The physical entanglement and chemical interaction that may be formed between the molecular chain structure of polyamide and the hexagonal boron nitride nanosheets not only improve the overall strength of the material, but also improve its heat resistance. This synergistic effect enables the composite material to maintain structural stability at higher temperatures while having excellent mechanical properties. In terms of barrier properties, the layered structure of hexagonal boron nitride nanosheets forms a circuitous diffusion path in the polyamide matrix, effectively extending the permeation path of gas molecules, thereby significantly improving the gas barrier properties of the film. At the same time, the high crystallinity and chemical stability of hexagonal boron nitride also help to enhance the barrier effect of the film against water vapor and other small molecules. The best balance of heat resistance, mechanical strength and barrier properties can be achieved through a carefully designed component ratio. The content of surface-modified layered hexagonal boron nitride nanosheets plays a decisive role in the performance of the composite material. The appropriate content can maximize its enhancement effect without excessively sacrificing the processing properties of the material. At the same time, the composition and proportion of the polyamide mixed powder can also be adjusted according to the specific application requirements to optimize the comprehensive performance of the material. In addition, the sophisticated preparation process plays a vital role in achieving these performance improvements. By controlling key process parameters such as mixing, dispersion and molding, the uniform distribution of surface-modified layered hexagonal boron nitride nanosheets in the polyamide matrix can be ensured to maximize their reinforcing effect. At the same time, appropriate processing conditions also help to form a good interface structure between the polyamide molecular chain and the nanosheets, further improving the overall performance of the material. This multi-component synergistic design concept not only achieves a comprehensive improvement in the heat resistance, mechanical strength and barrier properties of high-barrier films, but also provides innovative ideas for the development of new high-performance composite materials.Through the ingenious combination of surface-modified layered hexagonal boron nitride nanosheets and polyamide mixed powder, the present invention successfully overcomes the limitations of traditional single materials and opens up a new direction for the development of high-performance thin film materials.

[0020] Furthermore, the preparation method of the surface-modified microcrystalline cellulose is as follows: by weight, 4 to 9 parts of microcrystalline cellulose, 3.0 to 6.0 parts of lauric acid glyceride and 100 parts of a mixed solution of ethanol and deionized water in a mass ratio of 1:1 are mixed, and then ultrasonicated for 10 to 20 minutes, and then stirred at 40 to 60°C for 120 to 240 minutes, and then the solution is poured into a rotary evaporator to remove the remaining water / ethanol in the solution at 65 to 75°C and 50 Torr, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain surface-modified microcrystalline cellulose.

[0021] The invention adopts the design of ethylene-co-vinyl alcohol layer mainly to enhance the heat resistance, high strength and barrier properties of high barrier film. This technical solution cleverly combines the excellent properties of microcrystalline cellulose and surface-modified microcrystalline cellulose, and achieves comprehensive improvement of various performances through reasonable component ratio and sophisticated preparation process. In terms of material composition, the present invention uses microcrystalline cellulose as the main component to construct the skeleton structure of the ethylene-co-vinyl alcohol layer. Microcrystalline cellulose, as a natural polymer material, has excellent mechanical properties, thermal stability and barrier properties. Its unique fibrous structure and high crystallinity give the material good strength, toughness and dimensional stability. At the same time, the rich hydroxyl functional groups of microcrystalline cellulose give it good hydrophilicity and polarity, which is beneficial to improve the barrier properties of the material. In order to further enhance the compatibility and interfacial bonding between microcrystalline cellulose and ethylene-co-vinyl alcohol matrix, the present invention introduces surface-modified microcrystalline cellulose as a functional additive. The surface modification of microcrystalline cellulose by lauric acid glyceride not only helps to enhance the dispersibility of microcrystalline cellulose in the polymer matrix, but also enhances the physical interaction force between interfaces, and promotes stress transfer and heat diffusion. In terms of preparation process, the present invention adopts a solution blending method to prepare surface-modified microcrystalline cellulose. Lauric acid glyceride is fully contacted with microcrystalline cellulose in an ethanol / water mixed solvent, and the surface reaction is promoted by ultrasound and stirring. Subsequently, the solvent is removed by rotary evaporation and vacuum drying to obtain uniformly modified microcrystalline cellulose. This solution blending method can achieve uniform coating and chemical bonding of lauric acid glyceride on the surface of microcrystalline cellulose, ensuring the consistency and stability of the modification effect. In the ethylene-co-vinyl alcohol layer, the surface-modified microcrystalline cellulose effectively enhances the comprehensive performance of the material with its excellent mechanical properties, hydrophobic properties and barrier properties. Polyethylene wax plays multiple roles in the ethylene-vinyl alcohol copolymer composite layer containing surface-modified microcrystalline cellulose. It mainly acts as a lubricant and a dispersing aid to improve the processing performance of the material and the dispersion uniformity of microcrystalline cellulose. At the same time, polyethylene wax also acts as an interface regulator to enhance the bonding force between the filler and the matrix. The uniformly dispersed modified fibers can not only bear external loads, inhibit crack propagation, and improve the strength and toughness of the material, but also form a tight three-dimensional network structure in the polymer matrix, extend the permeation path of gas and water vapor, and significantly improve the barrier performance. It helps to improve the water resistance and dimensional stability of the material and reduce the impact of environmental humidity changes on the performance. In summary, the present invention constructs a high-performance ethylene-co-vinyl alcohol composite material through the synergistic effect of microcrystalline cellulose and surface-modified microcrystalline cellulose. Reasonable component ratio, surface modification strategy and solution blending process jointly promote the uniform dispersion and interface bonding of modified cellulose in the polymer matrix, and maximize its strengthening and toughening effect. The high crystallinity and excellent mechanical properties of microcrystalline cellulose give the material excellent thermal stability, strength and toughness.The design concept of this natural cellulose-based composite material provides a new approach for the development of high-barrier film materials and has broad application prospects.

[0022] Furthermore, the first adhesive resin layer or the second adhesive resin layer is polyethylene modified by maleic anhydride, and the maleic anhydride grafting rate is 0.5% to 2%.

[0023] The present invention adopts maleic anhydride modified polyethylene (MAH-PE) as the design of the adhesive resin layer of the high barrier film, which is mainly used to enhance the interlayer adhesion performance and overall barrier performance of the multilayer film structure. The design purpose of this technical solution is to achieve the synergistic optimization of multiple properties while maintaining the basic properties of the material. MAH-PE, as a special modified polymer, plays a key role in the preparation process of the high barrier film due to its unique molecular structure. First, the core advantage of MAH-PE lies in its excellent adhesion performance. The introduction of maleic anhydride groups enables this material to form chemical bonds with a variety of polar and non-polar materials, thereby significantly enhancing the interlayer adhesion. This characteristic makes MAH-PE an ideal choice for connecting materials of different properties, and is particularly suitable for effectively combining a non-polar material ethylene-vinyl alcohol copolymer composite layer with a polar material modified polyethylene layer. By enhancing interlayer adhesion, MAH-PE not only improves the overall strength of the multilayer film structure, but also helps to prevent interlayer peeling, thereby extending the service life of the product. Secondly, the use of MAH-PE can improve the barrier performance of the overall structure to a certain extent while improving adhesion. Although this is not its main function, this synergistic effect is of great significance for the performance optimization of high barrier films. By improving interlayer bonding, MAH-PE helps reduce micro defects, thereby indirectly improving the gas and water vapor barrier capacity of the film structure. In addition, the selection of MAH-PE also takes into account the processing performance and economy of the material. As a modified polyethylene, MAH-PE retains the excellent processing characteristics and flexibility of polyethylene, which makes it show good adaptability in the production process. At the same time, compared with other special adhesives, MAH-PE is generally more cost-effective, which is of great significance for large-scale production.

[0024] In the application of MAH-PE, the grafting rate of maleic anhydride is a key parameter that directly affects the performance and processing characteristics of the material. The present invention selects a grafting rate range of 0.5% to 2% to achieve the best balance between performance and processability. The lower limit of this range ensures sufficient adhesion, while the upper limit effectively avoids the cross-linking problem that may occur during processing. Too low a grafting rate will lead to insufficient bonding performance and fail to effectively connect materials of different properties; while too high a grafting rate may cause cross-linking, resulting in a sharp increase in material viscosity, affecting continuous production. The technical solution of the present invention also takes into account the effects of different material combinations and processing conditions on the performance of MAH-PE. By optimizing the grafting rate, it can be adjusted for different target materials and final product requirements to obtain the best bonding effect and overall performance. This flexibility makes the technical solution have a wide range of application potential. In general, the present invention successfully achieves multiple synergistic optimization of adhesion, barrier properties, processability and economy in high barrier films by carefully designing the application scheme of MAH-PE. This comprehensive consideration not only improves product performance, but also ensures the reliability and economic benefits of the production process, and provides new ideas and methods for the development and application of high-performance multilayer film structures.

[0025] Furthermore, the total thickness of the co-extruded high barrier film is 30~90μm, wherein the thickness ratio of the first modified polyethylene layer, the first adhesive resin layer, the first polyamide composite layer, the ethylene-vinyl alcohol copolymer composite layer, the second adhesive resin layer, the second polyamide composite layer and the second modified polyethylene layer is 3:5:3:6:3:5:3.

[0026] Furthermore, the first modified polyethylene layer and the second modified polyethylene layer are of the same material and prepared in the same method with equal thickness; the first polyamide composite layer and the second modified polyamide composite layer are of the same material and prepared in the same method with equal thickness; the first adhesive resin layer and the second adhesive resin layer are of the same material and prepared in the same method with equal thickness.

[0027] The present invention adopts a multi-layer co-extrusion structure design mainly to enhance the comprehensive performance of the high barrier film, including barrier properties, mechanical strength, heat resistance and overall stability. The co-extruded high barrier film adopts a seven-layer structure design, the total thickness is controlled within the range of 30~90μm, and the thickness ratio of each layer is 3:5:3:6:3:5:3. This special design has multiple purposes and advantages. First, the central layer adopts an ethylene-vinyl alcohol copolymer composite layer with the largest thickness ratio as the main barrier layer to effectively prevent the penetration of gas and water vapor. Secondly, the polyamide composite layer is located on both sides of the central layer, providing excellent mechanical strength and heat resistance. The modified polyethylene layer is the outermost layer, which gives the film good flexibility and sealing. The adhesive resin layer ensures the close bonding between the functional layers and enhances the overall structural stability. The design of this multi-layer structure fully considers the characteristics and interactions of each component material. The carboxyl functionalized graphene and epoxy soybean oil introduced in the modified polyethylene layer not only improve the heat resistance and mechanical strength of polyethylene, but also enhance its compatibility with the adhesive resin layer. The surface-modified layered hexagonal boron nitride nanosheets added to the polyamide composite layer can significantly improve the thermal conductivity and heat resistance of the film, while enhancing the mechanical properties. The central ethylene-vinyl alcohol copolymer composite layer further improves the barrier properties by introducing surface-modified microcrystalline cellulose, and may enhance the bonding strength with the adjacent layers. The thickness ratio design of each functional layer also reflects careful consideration. The central layer is thicker to ensure sufficient barrier effect; the polyamide composite layer and modified polyethylene layer on both sides are relatively thin, but through the symmetrical design, the overall structure is effectively balanced to avoid internal stress and warping problems caused by uneven thickness. This symmetrical design is also conducive to eliminating the thermal stress caused by the difference in thermal expansion coefficient and improving the stability of the film in a high temperature environment. In addition, the present invention pays special attention to the synergistic effect between the components in the design. For example, the carboxyl functionalized polyethylene in the modified polyethylene layer not only enhances the performance of the polyethylene matrix, but may also produce chemical interactions with the maleic anhydride modified polyethylene in the adhesive resin layer, further enhancing the interlayer bonding force. The surface-modified layered hexagonal boron nitride nanosheets in the polyamide composite layer may form a strong interaction with the polyamide, thereby improving the overall performance of the composite material. The microcrystalline cellulose in the ethylene-vinyl alcohol copolymer composite layer not only enhances the barrier properties, but may also enhance the bonding with adjacent layers through hydrogen bonding. Through this carefully designed multilayer structure and material combination, the high-barrier film of the present invention can have good mechanical strength, heat resistance and overall stability while maintaining excellent barrier properties. The synergistic effect between the functional layers and additives further enhances the comprehensive performance of the film, making it likely to be widely used in high-end packaging, electronic product packaging and other fields. At the same time, this design also provides new ideas and methods for the development of new high-performance multilayer functional film materials.

[0028] The present invention also provides a method for preparing a high-heat-resistant, high-strength, multi-layer co-extruded high-barrier film, comprising the following steps:

[0029] S1. Mixing raw materials: Under a nitrogen environment, the raw materials of each layer of the multi-layer co-extruded high barrier film are respectively prepared in proportion and put into a mixer for uniform mixing, and then respectively sent to an extruder for melting.

[0030] S2. Plasticizing extrusion: in the order of the layers of the high barrier film, the layers are co-extruded using an extruder, the extruder temperature of the first modified polyethylene layer and the second modified polyethylene layer is 182-190°C; the extruder temperature of the first adhesive resin layer and the second adhesive resin layer is 190-205°C; the extrusion temperature of the first polyamide composite layer and the first polyamide composite layer is 280-300°C; the extrusion temperature of the ethylene-vinyl alcohol copolymer composite layer is 200-220°C.

[0031] S3. Blow molding: The multi-layer molten film material coming out of the extruder is extruded through a circular die head, and cooling air is continuously introduced into the film bubble to make the film bubble expand evenly. The blowing ratio is adjusted to 2.5~3.5 to obtain ideal film thickness uniformity and transverse orientation. The die head temperature is controlled at 230~250℃ to ensure that each layer of material maintains good fluidity and interlayer bonding.

[0032] S4. Cooling and shaping: Use an efficient cooling system to quickly and evenly cool the film bubble, control the cooling air temperature to 15~25℃, and adjust the cooling wind speed to 8~12m / s. Ensure that the film bubble remains stable during the cooling process to avoid wrinkles or local deformation, and fold and flatten the film bubble when it is completely cooled to room temperature.

[0033] S5. Traction and winding: Use a precisely controlled traction roller system to traction the cooled and shaped film at a stable speed. The traction speed is controlled at 30~50m / min and is coordinated with the extrusion speed and blowing ratio to obtain the required longitudinal orientation and film thickness. A tension control system is used to keep the film tension at a constant level to avoid excessive stretching or relaxation. Finally, an automatic roll changing device is used to continuously wind up the formed multi-layer co-extruded high barrier film. The winding tension is controlled at 0.5~1.5N / cm to ensure that the roll structure is tight and uniform without bubbles and wrinkles.

[0034] The present invention also discloses the application of a high-heat-resistant and high-strength multi-layer co-extruded high-barrier film, which is applied to food packaging, electronic device packaging, pharmaceutical packaging and new energy battery packaging.

[0035] The present invention adopts the design of multi-layer co-extrusion structure mainly to enhance the heat resistance, mechanical strength and barrier properties of high barrier film. This technical solution realizes the synergy between each functional layer through a carefully designed multi-layer structure and preparation process, thereby significantly improving the comprehensive performance of the high barrier film. In terms of structural design, the present invention cleverly combines the modified polyethylene layer, the adhesive resin layer, the polyamide composite layer and the ethylene-vinyl alcohol copolymer composite layer. As the outer layer, the modified polyethylene layer not only provides good mechanical strength and flexibility, but also has excellent sealing and weather resistance. The introduction of the polyamide composite layer greatly improves the heat resistance of the film material, enabling it to remain stable under high temperature conditions. The ethylene-vinyl alcohol copolymer composite layer gives the film material excellent gas barrier properties, effectively preventing the penetration of small molecules such as oxygen and water vapor. The design of the adhesive resin layer ensures the firm bonding between the functional layers and improves the stability of the overall structure. The design of this multi-layer structure gives full play to the advantages of each material and achieves an overall improvement in performance through a synergistic effect. In terms of preparation process, the present invention adopts a finely controlled co-extrusion blow molding process. First, in the raw material mixing stage, the uniform dispersion of each component is ensured by mixing under a nitrogen environment, laying the foundation for subsequent processing. In the plasticizing and extruding stage, unique temperature parameters are set for different material layers, which not only ensures the full melting of each layer of material, but also maintains its characteristics, providing ideal conditions for subsequent molding. The key to the blow molding stage is to control the blow ratio and die temperature, which helps to achieve the ideal film thickness uniformity and orientation degree, while ensuring good bonding between the layers. The cooling and shaping stage adopts an efficient cooling system, which effectively prevents thermal stress accumulation and interlayer separation through rapid and uniform cooling, ensuring the dimensional stability of the finished product. Finally, in the traction and winding stage, the orientation performance and thickness distribution of the film material are further optimized by precisely controlling the traction speed and tension, while ensuring the quality stability of the finished product. This carefully designed preparation process not only ensures that the performance of each functional layer is fully utilized, but also achieves synergy between the layers through the optimization of process parameters. For example, proper temperature control and cooling process help to form an ideal interface structure and enhance the interlayer bonding force; while reasonable traction and orientation process optimizes the molecular chain arrangement and improves the overall mechanical properties and barrier properties.

[0036] The high heat-resistant and high-strength multi-layer co-extruded high-barrier film of the present invention has broad application prospects in the fields of food packaging, pharmaceutical packaging, and new energy battery packaging. In terms of food packaging, its excellent barrier properties can effectively extend the shelf life of food; in the field of pharmaceutical packaging, its stable chemical properties and excellent barrier properties can ensure the safety and effectiveness of drugs; and in terms of new energy battery packaging, its excellent heat resistance and barrier properties can significantly improve the safety and service life of the battery. These applications fully demonstrate the important value of the present invention in improving product performance, extending service life, and enhancing safety. In short, the present invention has successfully developed a high heat-resistant and high-strength multi-layer co-extruded high-barrier film with excellent performance through the synergistic effect of multi-layer structure design and fine preparation process. The film material performs well in terms of heat resistance, mechanical strength and barrier properties, providing a new method for technological progress and product upgrading in related fields.

[0037] (3) Beneficial technical effects

[0038] 1. The present invention significantly improves the heat resistance, mechanical strength and barrier properties of high barrier films through innovative design and preparation of the first modified polyethylene. Compared with the prior art, the present invention exhibits unique advantages in many aspects: first, the coordinated use of low-density polyethylene and linear low-density polyethylene gives full play to the complementary characteristics of the two materials, laying a high-quality foundation for subsequent modifications; second, the introduction of carboxyl functionalized graphene not only improves the polarity and reactivity of the material, but also enhances the interfacial bonding force by forming covalent bonds, effectively improving the mechanical properties and barrier properties; third, the clever use of epoxy soybean oil as a high-efficiency dispersant and compatibilizer significantly improves the dispersibility of graphene and its compatibility with the polymer matrix, while giving the material excellent flexibility and impact resistance. This multi-component synergistic enhancement design concept solves the problem that traditional high barrier films are difficult to balance in terms of heat resistance, mechanical strength and barrier properties, and performs excellently in practical applications.

[0039] 2. The present invention significantly improves the heat resistance, mechanical strength and barrier properties of the high barrier film by innovatively designing the first polyamide layer. Compared with the prior art, the present invention has the following unique advantages: First, the coordinated use of polyamide 66 and polyamide 6 gives full play to the complementary characteristics of the two materials, laying a high-quality foundation for composite materials; second, the introduction of surface-modified layered hexagonal boron nitride nanosheets not only improves the mechanical properties and thermal conductivity of the material, but also significantly enhances the barrier properties by forming a tortuous barrier path; third, 3-aminopropyltriethoxysilane is used for surface modification, which greatly improves the compatibility and interfacial bonding between the nanosheets and the polyamide matrix. This multi-component synergistic enhancement design concept solves the problem that traditional high barrier films are difficult to balance in terms of heat resistance, mechanical strength and barrier properties.

[0040] 3. The present invention significantly improves the heat resistance, mechanical strength and barrier properties of the high barrier film by innovatively designing the ethylene-co-vinyl alcohol layer. Compared with the prior art, the present invention has the following outstanding advantages: First, the high crystallinity and excellent mechanical properties of microcrystalline cellulose are used to construct the skeleton structure, laying a solid foundation for the composite material; second, surface-modified microcrystalline cellulose is introduced as a functional additive, and the compatibility and interfacial bonding force with the matrix are improved by modification with lauric acid glyceride; third, the surface-modified microcrystalline cellulose is prepared by a solution blending method, ensuring the consistency and stability of the modification effect. This multi-component synergistic enhancement design concept solves the problem that traditional high barrier films are difficult to balance in terms of heat resistance, mechanical strength and barrier properties.

[0041] 4. The present invention uses maleic anhydride modified polyethylene (MAH-PE) as the adhesive resin layer of the high barrier film, which significantly improves the interlayer adhesion performance and overall barrier performance of the multilayer film structure. Compared with the prior art, the present invention has the following outstanding advantages: First, the unique molecular structure of MAH-PE enables it to form chemical bonds with a variety of polar and non-polar materials, significantly enhancing the interlayer adhesion, improving the overall strength of the multilayer film, effectively preventing interlayer peeling, and extending the product life. Secondly, by improving the interlayer bonding, the barrier ability of the film structure to gas and water vapor is indirectly improved, and the barrier performance is improved. Thirdly, MAH-PE retains the excellent processing characteristics and flexibility of polyethylene, and at the same time has high cost-effectiveness, which can reduce production costs. In practical applications, the present invention solves the problems of insufficient interlayer adhesion and poor barrier performance in traditional multilayer film structures.

[0042] 5. The present invention adopts a multi-layer co-extrusion structure design and successfully develops a high-heat-resistant and high-strength multi-layer co-extruded high-barrier film, which significantly improves the comprehensive performance of the film material. Compared with the prior art, the present invention has innovations in structural design and preparation process, and realizes the synergy between the functional layers, thereby greatly improving the heat resistance, mechanical strength and gas barrier properties of the film material. The modified polyethylene outer layer provides excellent sealing and weather resistance, the polyamide composite layer greatly improves the heat resistance, and the ethylene-vinyl alcohol copolymer composite layer significantly improves the gas barrier properties. Innovative preparation processes, such as uniform mixing under a nitrogen environment, precisely controlled temperature parameters and an efficient cooling system, ensure the optimal performance of each functional layer, while improving the uniformity of film thickness and interlayer bonding strength. Precise control in the traction and winding stage further optimizes the orientation performance and thickness distribution of the film material. This multi-layer structure not only solves the shortcomings of traditional single-layer films in performance, but also achieves overall optimization of performance through the synergy of each layer. The present invention has broad application prospects and performs well in the fields of food packaging, pharmaceutical packaging and new energy battery packaging. In terms of food packaging, it can significantly extend the shelf life of food; in the field of pharmaceutical packaging, it can effectively improve the stability of drugs; in the packaging of new energy batteries, it can significantly improve the safety and service life of batteries. This high-performance film material not only performs well in traditional application fields, but also shows great potential in emerging high-tech fields, providing new solutions for the technological upgrading and innovative development of related industries, and promoting the progress of the field of high-performance functional materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is the infrared Fourier spectrum FTIR graph of the carboxyl functionalized graphene prepared in Example 1 of the present invention.

[0044] Figure 2 This is the infrared Fourier spectrum FTIR graph of the carboxyl functionalized polyethylene prepared in Example 1 of the present invention.

[0045] Figure 3 This is the infrared Fourier spectrum FTIR graph of the modified polyethylene layer prepared in Example 1 of the present invention.

[0046] Figure 4 This is a TEM transmission electron microscope image of the carboxyl-functionalized graphene in the modified polyethylene prepared in Example 1 of the present invention.

[0047] Figure 5 This is a TEM transmission electron microscope image of the surface modified layered hexagonal boron nitride nanosheets prepared in Example 1 of the present invention.

[0048] Figure 6 This is the phase analysis XRD spectrum of the surface modified layered hexagonal boron nitride nanosheets prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0049] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0050] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0051] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies

[0052]

[0053] Example 1

[0054] A high heat-resistant and high-strength multi-layer co-extruded high-barrier film, comprising seven layers of film in contact with each other, which are, in order, a first modified polyethylene layer, a first adhesive resin layer, a first polyamide composite layer, an ethylene-vinyl alcohol copolymer composite layer, a second adhesive resin layer, a second polyamide composite layer and a second modified polyethylene layer;

[0055] The first modified polyethylene layer or the second modified polyethylene layer is prepared from the following components in parts by weight: 2 parts of carboxyl functionalized graphene, 0.8 parts of epoxy soybean oil, 40 parts of carboxyl functionalized polyethylene and 0.5 parts of sodium dodecylbenzene sulfonate.

[0056] The first polyamide composite layer or the second polyamide composite layer is prepared from the following components by weight: 3.0 parts of surface-modified layered hexagonal boron nitride nanosheets and 60 parts of polyamide mixed powder. The polyamide mixed powder is a mixture of polyamide 66 and polyamide 6 in a mass ratio of 6:4.

[0057] The ethylene-vinyl alcohol copolymer composite layer is prepared from the following components in parts by weight: 100 parts of ethylene-vinyl alcohol copolymer, 2.0 parts of surface-modified microcrystalline cellulose and 0.3 parts of polyethylene wax.

[0058] The preparation method of the carboxyl functionalized polyethylene of the present embodiment is as follows: in parts by weight, 100 parts of mixed polyethylene, 300 parts of xylene and 0.1 parts of diisopropylbenzene peroxide are mixed evenly, and then 5 parts of acrylic acid are added, and the mixture is heated to 120°C under a nitrogen atmosphere, and then stirred for reaction for 120 minutes. After the reaction is completed, the cooled reaction solution is slowly injected dropwise into 200 parts of methanol, at which time the target product can be observed to precipitate as a white flocculent precipitate, and then the precipitated product is collected by vacuum filtration separation technology, and the precipitated product is washed 3 times with methanol, and finally, the wet precipitated product is placed in a vacuum drying device and dried at 50°C for 12 hours to constant weight to obtain the desired carboxyl functionalized polyethylene, and the mixed polyethylene is composed of low-density polyethylene and linear low-density polyethylene in a mass ratio of 4:6.

[0059] The preparation method of carboxyl functionalized graphene in this embodiment is as follows: First, 5 parts of graphene oxide are added to 200 parts of deionized water at 150 °C. W power for 120 min to form a colloidal dispersion, then, 40 parts of hydrazine hydrate were slowly added dropwise to the dispersion, the reaction mixture was stirred under reflux conditions for 6 h, and then the precipitated product was collected by filtration, and then the precipitated product was washed with deionized water 3 times, and then dried in a 50°C vacuum drying oven to constant weight to obtain chemically reduced graphene oxide; next, 6 parts of chemically reduced graphene oxide and 200 parts of toluene were mixed evenly, and 20 parts of azobisisobutyronitrile were added, and vigorously stirred at 70°C for 240 min under an argon atmosphere, and then the solution was cooled to room temperature and the precipitate was collected by filtering the solution, and the precipitate was washed with toluene 3 times, and then the wet precipitated product was placed in a vacuum drying device, and cyano-modified chemically reduced graphene oxide was obtained at room temperature to constant weight; then, 10 parts of cyano-modified chemically reduced graphene oxide were dispersed in 100 parts of methanol, and 100 parts of 10 mol / L sodium hydroxide aqueous solution, reflux and stir at 55°C for 10h, then filter the reaction mixture to collect the precipitated product, wash the precipitated product with deionized water 3 times, then wash it with 1mol / L hydrochloric acid three times, and continue to wash it with a large amount of deionized water until it is neutral. Finally, the obtained solid is dried in a vacuum drying oven at 50°C to constant weight to obtain the target product, carboxyl functionalized graphene.

[0060] The preparation method of the surface modified layered hexagonal boron nitride nanosheets of this embodiment is as follows: in parts by weight, 2 parts of layered hexagonal boron nitride nanosheets and 50 parts of anhydrous ethanol are mixed, and ultrasonic dispersion is performed for 30 minutes to obtain solution A; then 1.0 part of 3-aminopropyltriethoxysilane is dissolved in 50 parts of anhydrous ethanol, and stirred evenly to obtain solution B; solution B is slowly added dropwise to solution A, and refluxed at 60°C for 4 hours; after the reaction is completed, the solid powder is collected by centrifugation, and then the solid powder is washed twice with anhydrous ethanol, and finally the wet solid powder is dried in a vacuum drying oven at 40°C for 12 hours to obtain surface modified layered hexagonal boron nitride nanosheets.

[0061] The preparation method of the surface-modified microcrystalline cellulose of this embodiment is as follows: by weight, 4 parts of microcrystalline cellulose, 3.0 parts of laurin and 100 parts of a mixed solution of ethanol and deionized water in a mass ratio of 1:1 are mixed, ultrasonicated for 10 minutes, and then stirred at 40°C for 120 minutes, and then the solution is poured into a rotary evaporator to remove the remaining water / ethanol in the solution at 65°C and 50 Torr, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain surface-modified microcrystalline cellulose.

[0062] The first adhesive resin layer or the second adhesive resin layer of this embodiment is polyethylene modified with maleic anhydride, and the maleic anhydride grafting rate is 0.5%.

[0063] The total thickness of the co-extruded high barrier film of this embodiment is 30 μm, wherein the thickness ratio of the first modified polyethylene layer, the first adhesive resin layer, the first polyamide composite layer, the ethylene-vinyl alcohol copolymer composite layer, the second adhesive resin layer, the second polyamide composite layer and the second modified polyethylene layer is 3:5:3:6:3:5:3. The first modified polyethylene layer and the second modified polyethylene layer are of the same material and the same preparation method with equal thickness; the first polyamide composite layer and the second modified polyamide composite layer are of the same material and the same preparation method with equal thickness; the first adhesive resin layer and the second adhesive resin layer are of the same material and the same preparation method with equal thickness.

[0064] This embodiment also provides a method for preparing a high-heat-resistant, high-strength, multi-layer co-extruded high-barrier film, comprising the following steps:

[0065] S1. Mixing raw materials: Under a nitrogen environment, the raw materials of each layer of the multi-layer co-extruded high barrier film are respectively prepared in proportion and put into a mixer for uniform mixing, and then respectively sent to an extruder for melting.

[0066] S2. Plasticizing extrusion: extrude the layers of the high barrier film in order using an extruder. The extruder temperature of the first modified polyethylene layer and the second modified polyethylene layer is 182°C; the extruder temperature of the first adhesive resin layer and the second adhesive resin layer is 190°C; the extrusion temperature of the first polyamide composite layer and the first polyamide composite layer is 280°C; the extrusion temperature of the ethylene-vinyl alcohol copolymer composite layer is 200°C.

[0067] S3. Blow molding: The multi-layer molten film material coming out of the extruder is extruded through a circular die head, and cooling air is continuously introduced into the film bubble to make the film bubble expand evenly. The blowing ratio is adjusted to 2.5 to obtain ideal film thickness uniformity and transverse orientation. The die head temperature is controlled at 230°C to ensure that each layer of material maintains good fluidity and interlayer bonding.

[0068] S4. Cooling and shaping: Use an efficient cooling system to quickly and evenly cool the film bubble, control the cooling air temperature to 15°C, and adjust the cooling wind speed to 8m / s. Ensure that the film bubble remains stable during the cooling process to avoid wrinkles or local deformation, and fold and flatten the film bubble when it is completely cooled to room temperature.

[0069] S5. Traction and winding: Use a precisely controlled traction roller system to traction the cooled and shaped film at a stable speed. The traction speed is controlled at 30m / min and is coordinated with the extrusion speed and blow-up ratio to obtain the required longitudinal orientation and film thickness. A tension control system is used to keep the film tension at a constant level to avoid excessive stretching or relaxation. Finally, an automatic roll-changing device is used to continuously wind up the formed multi-layer co-extruded high-barrier film. The winding tension is controlled at 0.5N / cm to ensure that the roll structure is tight and uniform without bubbles and wrinkles.

[0070] Through characterization methods such as infrared Fourier spectrum FTIR, transmission electron microscope TEM and X-ray diffraction XRD, it can be proved that Example 1 of the present invention successfully prepared carboxyl functionalized graphene, carboxyl functionalized polyethylene and modified polyethylene layer. Figure 1 and Figure 2 The FTIR spectra of carboxyl functionalized polyethylene and carboxyl functionalized graphene show that the -1 There are obvious carboxyl-OH characteristic peaks near the -1 The C=O stretching vibration peak in the range indicates that the carboxyl group has been successfully grafted onto polyethylene and graphene. Figure 3 The FTIR spectrum of the modified polyethylene layer is at 3400 cm -1 The strong -OH absorption peak at 40° further confirmed the successful combination of carboxyl-functionalized polyethylene and carboxyl-functionalized graphene through the -COOH group. Figure 4The TEM images clearly show the graphene sheets uniformly dispersed in the polyethylene matrix, indicating that after carboxyl functionalization, graphene and polyethylene have good compatibility. Figure 5 and Figure 6 The TEM and XRD characterization results prove the successful preparation of layered hexagonal boron nitride nanosheets. In summary, Example 1 of the present invention successfully prepared a carboxyl functionalized graphene / polyethylene composite material with high dispersibility and compatibility through a reasonable chemical reaction route and process conditions, laying a foundation for the development of high-performance polyolefin-based composite materials.

[0071] Example 2

[0072] A high heat-resistant and high-strength multi-layer co-extruded high-barrier film, comprising seven layers of film in contact with each other, which are, in order, a first modified polyethylene layer, a first adhesive resin layer, a first polyamide composite layer, an ethylene-vinyl alcohol copolymer composite layer, a second adhesive resin layer, a second polyamide composite layer and a second modified polyethylene layer;

[0073] The first modified polyethylene layer or the second modified polyethylene layer is prepared from the following components in parts by weight: 2 parts of carboxyl functionalized graphene, 1 part of epoxy soybean oil, 46 parts of carboxyl functionalized polyethylene and 0.6 parts of sodium dodecylbenzene sulfonate.

[0074] The first polyamide composite layer or the second polyamide composite layer is prepared from the following components by weight: 3.9 parts of surface modified layered hexagonal boron nitride nanosheets, 0.4 parts of erucic acid amide and 66 parts of polyamide mixed powder. The polyamide mixed powder is prepared by mixing polyamide 66 and polyamide 6 in a mass ratio of 5.4:4.6.

[0075] The ethylene-vinyl alcohol copolymer composite layer is prepared from the following components in parts by weight: 100 parts of ethylene-vinyl alcohol copolymer, 2.8 parts of surface-modified microcrystalline cellulose and 0.4 parts of polyethylene wax.

[0076] The preparation method of the carboxyl functionalized polyethylene of the present embodiment is as follows: in parts by weight, 100 parts of mixed polyethylene, 360 parts of xylene and 0.2 parts of diisopropylbenzene peroxide are mixed evenly, and then 8 parts of acrylic acid are added, and the mixture is heated to 129°C under a nitrogen atmosphere, and then stirred for reaction for 156 minutes. After the reaction is completed, the cooled reaction solution is slowly injected dropwise into 200 parts of methanol, at which time the target product can be observed to precipitate as a white flocculent precipitate, and then the obtained precipitated product is collected by vacuum filtration separation technology, and the precipitated product is washed 3 times with methanol, and finally, the wet precipitated product is placed in a vacuum drying device, and dried at 53°C for 5 hours to constant weight to obtain the desired carboxyl functionalized polyethylene, and the mixed polyethylene is composed of low-density polyethylene and linear low-density polyethylene in a mass ratio of 4.6:5.4.

[0077] The preparation method of carboxyl functionalized graphene in this embodiment is as follows: first, 6.5 parts of graphene oxide are added to 200 parts of deionized water at 150 °C. W power for 156 min to form a colloidal dispersion, then, 40 parts of hydrazine hydrate were slowly added dropwise to the dispersion, the reaction mixture was stirred under reflux conditions for 7.8 h, and then the precipitated product was collected by filtration, and then the precipitated product was washed with deionized water 3 times, and then dried in a vacuum drying oven at 54.5°C to constant weight to obtain chemically reduced graphene oxide; next, 7.8 parts of chemically reduced graphene oxide and 200 parts of toluene were mixed evenly, and 22.4 parts of azobisisobutyronitrile were added, and vigorously stirred at 73°C for 240 min under an argon atmosphere, and then the solution was cooled to room temperature and the precipitate was collected by filtering the solution, and the precipitate was washed with toluene 3 times, and then the wet precipitated product was placed in a vacuum drying device to obtain cyano-modified chemically reduced graphene oxide at room temperature to constant weight; then, 11.8 parts of cyano-modified chemically reduced graphene oxide were dispersed in 100 parts of methanol, and 100 parts of 10 mol / L sodium hydroxide aqueous solution, reflux and stir at 58°C for 13h, then filter the reaction mixture to collect the precipitated product, wash the precipitated product with deionized water 3 times, then wash it with 1mol / L hydrochloric acid three times, and continue to wash it with a large amount of deionized water until it is neutral. Finally, the obtained solid is dried in a vacuum drying oven at 50°C to constant weight to obtain the target product, carboxyl functionalized graphene.

[0078] The preparation method of the surface modified layered hexagonal boron nitride nanosheets of this embodiment is as follows: in parts by weight, 3.2 parts of layered hexagonal boron nitride nanosheets and 65 parts of anhydrous ethanol are mixed, and ultrasonic dispersion is performed for 39 minutes to obtain solution A; then 1.6 parts of 3-aminopropyltriethoxysilane are dissolved in 65 parts of anhydrous ethanol, and stirred evenly to obtain solution B; solution B is slowly added dropwise to solution A, and refluxed at 66°C for 5.2 hours; after the reaction is completed, the solid powder is collected by centrifugation, and then the solid powder is washed twice with anhydrous ethanol, and finally the wet solid powder is dried in a vacuum drying oven at 46°C for 15.6 hours to obtain surface modified layered hexagonal boron nitride nanosheets.

[0079] The preparation method of the surface-modified microcrystalline cellulose of this embodiment is as follows: in parts by weight, 5 parts of microcrystalline cellulose, 3.9 parts of laurin and 100 parts of a mixed solution of ethanol and deionized water in a mass ratio of 1:1 are mixed, ultrasonicated for 13 minutes, and then stirred at 46°C for 156 minutes, and then the solution is poured into a rotary evaporator to remove the remaining water / ethanol in the solution at 68°C and 50 Torr, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain surface-modified microcrystalline cellulose.

[0080] The first adhesive resin layer or the second adhesive resin layer of this embodiment is polyethylene modified with maleic anhydride, and the maleic anhydride grafting rate is 0.9%.

[0081] The total thickness of the co-extruded high barrier film of this embodiment is 48 μm, wherein the thickness ratio of the first modified polyethylene layer, the first adhesive resin layer, the first polyamide composite layer, the ethylene-vinyl alcohol copolymer composite layer, the second adhesive resin layer, the second polyamide composite layer and the second modified polyethylene layer is 3:5:3:6:3:5:3. The first modified polyethylene layer and the second modified polyethylene layer are of the same material and the same preparation method with equal thickness; the first polyamide composite layer and the second modified polyamide composite layer are of the same material and the same preparation method with equal thickness; the first adhesive resin layer and the second adhesive resin layer are of the same material and the same preparation method with equal thickness.

[0082] This embodiment also provides a method for preparing a high-heat-resistant, high-strength, multi-layer co-extruded high-barrier film, comprising the following steps:

[0083] S1. Mixing raw materials: Under a nitrogen environment, the raw materials of each layer of the multi-layer co-extruded high barrier film are respectively prepared in proportion and put into a mixer for uniform mixing, and then respectively sent to an extruder for melting.

[0084] S2. Plasticizing extrusion: in the order of the layers of the high barrier film, the layers are co-extruded using an extruder, the extruder temperature of the first modified polyethylene layer and the second modified polyethylene layer is 184°C; the extruder temperature of the first adhesive resin layer and the second adhesive resin layer is 195°C; the extrusion temperature of the first polyamide composite layer and the first polyamide composite layer is 286°C; the extrusion temperature of the ethylene-vinyl alcohol copolymer composite layer is 206°C.

[0085] S3. Blow molding: The multi-layer molten film material coming out of the extruder is extruded through a circular die head, and cooling air is continuously introduced into the film bubble to make the film bubble expand evenly. The blowing ratio is adjusted to 2.8 to obtain ideal film thickness uniformity and transverse orientation. The die head temperature is controlled at 236°C to ensure that each layer of material maintains good fluidity and interlayer bonding.

[0086] S4. Cooling and shaping: Use an efficient cooling system to quickly and evenly cool the film bubble, control the cooling air temperature to 18°C, and adjust the cooling wind speed to 9.2m / s. Ensure that the film bubble remains stable during the cooling process to avoid wrinkles or local deformation, and fold and flatten the film bubble when it is completely cooled to room temperature.

[0087] S5. Traction and winding: Use a precisely controlled traction roller system to traction the cooled and shaped film at a stable speed. The traction speed is controlled at 36m / min and is coordinated with the extrusion speed and blow-up ratio to obtain the required longitudinal orientation and film thickness. A tension control system is used to keep the film tension at a constant level to avoid excessive stretching or relaxation. Finally, an automatic roll-changing device is used to continuously wind up the formed multi-layer co-extruded high-barrier film. The winding tension is controlled at 0.8N / cm to ensure that the roll structure is tight and uniform without bubbles and wrinkles.

[0088] Example 3

[0089] A high heat-resistant and high-strength multi-layer co-extruded high-barrier film, comprising seven layers of film in contact with each other, which are, in order, a first modified polyethylene layer, a first adhesive resin layer, a first polyamide composite layer, an ethylene-vinyl alcohol copolymer composite layer, a second adhesive resin layer, a second polyamide composite layer and a second modified polyethylene layer;

[0090] The first modified polyethylene layer or the second modified polyethylene layer is prepared from the following components in parts by weight: 2 parts of carboxyl functionalized graphene, 0.6 parts of epoxy soybean oil, 52 parts of carboxyl functionalized polyethylene and 0.8 parts of sodium dodecylbenzene sulfonate.

[0091] The first polyamide composite layer or the second polyamide composite layer is prepared from the following components by weight: 4.8 parts of surface-modified layered hexagonal boron nitride nanosheets, 0.5 parts of erucic acid amide and 72 parts of polyamide mixed powder. The polyamide mixed powder is prepared by mixing polyamide 66 and polyamide 6 in a mass ratio of 5:5.

[0092] The ethylene-vinyl alcohol copolymer composite layer is prepared from the following components in parts by weight: 100 parts of ethylene-vinyl alcohol copolymer, 3.5 parts of surface-modified microcrystalline cellulose and 0.7 parts of polyethylene wax.

[0093] The preparation method of the carboxyl functionalized polyethylene of the present embodiment is as follows: in parts by weight, 100 parts of mixed polyethylene, 420 parts of xylene and 0.3 parts of diisopropylbenzene peroxide are mixed evenly, and then 11 parts of acrylic acid are added, and the mixture is heated to 138°C under a nitrogen atmosphere, and then stirred for reaction for 192 minutes. After the reaction is completed, the cooled reaction solution is slowly injected dropwise into 200 parts of methanol, at which time the target product can be observed to precipitate as a white flocculent precipitate, and then the precipitated product is collected by vacuum filtration separation technology, and the precipitated product is washed 3 times with methanol, and finally, the wet precipitated product is placed in a vacuum drying device, and dried at 56°C for 19 hours to constant weight to obtain the desired carboxyl functionalized polyethylene, and the mixed polyethylene is composed of low-density polyethylene and linear low-density polyethylene in a mass ratio of 5:5.

[0094] The preparation method of carboxyl functionalized graphene in this embodiment is as follows: First, 8 parts of graphene oxide are added to 200 parts of deionized water at 150 °C. W power for 192 min to form a colloidal dispersion, then, 40 parts of hydrazine hydrate were slowly added dropwise to the dispersion, the reaction mixture was stirred under reflux conditions for 9 h, and then the precipitated product was collected by filtration, and then the precipitated product was washed with deionized water 3 times, and then dried in a 59°C vacuum drying oven to constant weight to obtain chemically reduced graphene oxide; next, 9.6 parts of chemically reduced graphene oxide and 200 parts of toluene were mixed evenly, and 24.8 parts of azobisisobutyronitrile were added, and vigorously stirred at 76°C for 240 min under an argon atmosphere, and then the solution was cooled to room temperature and the precipitate was filtered to collect the precipitate, and the precipitate was washed with toluene 3 times, and the wet precipitate was placed in a vacuum drying device to obtain cyano-modified chemically reduced graphene oxide at room temperature to constant weight; then, 13.6 parts of cyano-modified chemically reduced graphene oxide were dispersed in 100 parts of methanol, and 1000 parts of 10 mol / L sodium hydroxide aqueous solution, reflux and stir at 61°C for 16h, then filter the reaction mixture to collect the precipitated product, wash the precipitated product with deionized water 3 times, then wash it with 1mol / L hydrochloric acid three times, and continue to wash it with a large amount of deionized water until it is neutral. Finally, the obtained solid is dried in a vacuum drying oven at 50°C to constant weight to obtain the target product, carboxyl functionalized graphene.

[0095] The preparation method of the surface modified layered hexagonal boron nitride nanosheets of this embodiment is as follows: in parts by weight, 4.4 parts of layered hexagonal boron nitride nanosheets and 80 parts of anhydrous ethanol are mixed, and ultrasonic dispersion is performed for 48 minutes to obtain solution A; then 2.2 parts of 3-aminopropyltriethoxysilane are dissolved in 80 parts of anhydrous ethanol, and stirred evenly to obtain solution B; solution B is slowly added dropwise to solution A, and refluxed at 72°C for 6 hours; after the reaction is completed, the solid powder is collected by centrifugation, and then the solid powder is washed twice with anhydrous ethanol, and finally the wet solid powder is dried in a vacuum drying oven at 52°C for 19 hours to obtain surface modified layered hexagonal boron nitride nanosheets.

[0096] The preparation method of the surface-modified microcrystalline cellulose of this embodiment is as follows: by weight, 6 parts of microcrystalline cellulose, 4.8 parts of laurin and 100 parts of a mixed solution of ethanol and deionized water in a mass ratio of 1:1 are mixed, ultrasonicated for 16 minutes, and then stirred at 52°C for 192 minutes, and then the solution is poured into a rotary evaporator to remove the remaining water / ethanol in the solution at 71°C and 50 Torr, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain surface-modified microcrystalline cellulose.

[0097] The first adhesive resin layer or the second adhesive resin layer of this embodiment is polyethylene modified with maleic anhydride, and the maleic anhydride grafting rate is 1.4%.

[0098] The total thickness of the co-extruded high barrier film of this embodiment is 66 μm, wherein the thickness ratio of the first modified polyethylene layer, the first adhesive resin layer, the first polyamide composite layer, the ethylene-vinyl alcohol copolymer composite layer, the second adhesive resin layer, the second polyamide composite layer and the second modified polyethylene layer is 3:5:3:6:3:5:3. The first modified polyethylene layer and the second modified polyethylene layer are made of the same material and prepared in the same method with equal thickness; the first polyamide composite layer and the second modified polyamide composite layer are made of the same material and prepared in the same method with equal thickness; the first adhesive resin layer and the second adhesive resin layer are made of the same material and prepared in the same method with equal thickness.

[0099] This embodiment also provides a method for preparing a high-heat-resistant, high-strength, multi-layer co-extruded high-barrier film, comprising the following steps:

[0100] S1. Mixing raw materials: Under a nitrogen environment, the raw materials of each layer of the multi-layer co-extruded high barrier film are respectively prepared in proportion and put into a mixer for uniform mixing, and then respectively sent to an extruder for melting.

[0101] S2. Plasticizing extrusion: in the order of the layers of the high barrier film, the layers are co-extruded using an extruder, the extruder temperature of the first modified polyethylene layer and the second modified polyethylene layer is 186°C; the extruder temperature of the first adhesive resin layer and the second adhesive resin layer is 199°C; the extrusion temperature of the first polyamide composite layer and the first polyamide composite layer is 292°C; the extrusion temperature of the ethylene-vinyl alcohol copolymer composite layer is 212°C.

[0102] S3. Blow molding: The multi-layer molten film material coming out of the extruder is extruded through a circular die head, and cooling air is continuously introduced into the film bubble to make the film bubble expand evenly. The blowing ratio is adjusted to 3.1 to obtain ideal film thickness uniformity and transverse orientation. The die head temperature is controlled at 242°C to ensure that each layer of material maintains good fluidity and interlayer bonding.

[0103] S4. Cooling and shaping: Use an efficient cooling system to quickly and evenly cool the film bubble, control the cooling air temperature to 21°C, and adjust the cooling wind speed to 10.4m / s. Ensure that the film bubble remains stable during the cooling process to avoid wrinkles or local deformation, and fold and flatten the film bubble when it is completely cooled to room temperature.

[0104] S5. Traction and winding: Use a precisely controlled traction roller system to traction the cooled and shaped film at a stable speed. The traction speed is controlled at 42m / min and coordinated with the extrusion speed and blow-up ratio to obtain the required longitudinal orientation and film thickness. A tension control system is used to keep the film tension at a constant level to avoid excessive stretching or relaxation. Finally, an automatic roll-changing device is used to continuously wind up the formed multi-layer co-extruded high-barrier film. The winding tension is controlled at 1.1N / cm to ensure that the roll structure is tight and uniform without bubbles and wrinkles.

[0105] Example 4

[0106] A high heat-resistant and high-strength multi-layer co-extruded high-barrier film, comprising seven layers of film in contact with each other, which are, in order, a first modified polyethylene layer, a first adhesive resin layer, a first polyamide composite layer, an ethylene-vinyl alcohol copolymer composite layer, a second adhesive resin layer, a second polyamide composite layer and a second modified polyethylene layer;

[0107] The first modified polyethylene layer or the second modified polyethylene layer is prepared from the following components by weight: 2 parts of carboxyl functionalized graphene, 0.8 parts of epoxidized soybean oil, 60 parts of carboxyl functionalized polyethylene and 1 part of sodium dodecylbenzene sulfonate. The mass ratio of the carboxyl functionalized graphene to the carboxyl functionalized polyethylene is 1:30.

[0108] The first polyamide composite layer or the second polyamide composite layer is prepared from the following components by weight: 6.0 parts of surface-modified layered hexagonal boron nitride nanosheets, 0.6 parts of erucic acid amide and 80 parts of polyamide mixed powder. The polyamide mixed powder is prepared by mixing polyamide 66 and polyamide 6 in a mass ratio of 4:6.

[0109] The ethylene-vinyl alcohol copolymer composite layer is prepared from the following components in parts by weight: 100 parts of ethylene-vinyl alcohol copolymer, 4.5 parts of surface-modified microcrystalline cellulose and 0.8 parts of polyethylene wax.

[0110] The preparation method of the carboxyl functionalized polyethylene of the present embodiment is as follows: in parts by weight, 100 parts of mixed polyethylene, 500 parts of xylene and 0.5 parts of diisopropylbenzene peroxide are mixed evenly, and then 15 parts of acrylic acid are added, and the mixture is heated to 150°C under a nitrogen atmosphere, and then stirred for reaction for 240 minutes. After the reaction is completed, the cooled reaction solution is slowly injected dropwise into 200 parts of methanol, at which time the target product can be observed to precipitate as a white flocculent precipitate, and then the precipitated product is collected by vacuum filtration separation technology, and the precipitated product is washed 3 times with methanol, and finally, the wet precipitated product is placed in a vacuum drying device, and dried at 60°C for 24 hours to constant weight to obtain the desired carboxyl functionalized polyethylene, and the mixed polyethylene is composed of low-density polyethylene and linear low-density polyethylene in a mass ratio of 4:6.

[0111] The preparation method of carboxyl functionalized graphene in this embodiment is as follows: first, 10 parts of graphene oxide are added to 200 parts of deionized water at 150 °C. W power for 240 min to form a colloidal dispersion, then, 40 parts of hydrazine hydrate were slowly added to the dispersion, the reaction mixture was stirred under reflux conditions for 12 h, and then the precipitated product was collected by filtration, and then the precipitated product was washed with deionized water 3 times, and then dried in a 65°C vacuum drying oven to constant weight to obtain chemically reduced graphene oxide; next, 12 parts of chemically reduced graphene oxide and 200 parts of toluene were mixed evenly, and 28 parts of azobisisobutyronitrile were added, and vigorously stirred at 80°C for 240 min under an argon atmosphere, and then the solution was cooled to room temperature and the solution was filtered to collect the precipitate, and the precipitate was washed with toluene 3 times, and then the wet precipitate was placed in a vacuum drying device to obtain cyano-modified chemically reduced graphene oxide at room temperature to constant weight; then, 16 parts of cyano-modified chemically reduced graphene oxide were dispersed in 100 parts of methanol, and 1000 parts of 10 mol / L sodium hydroxide aqueous solution, reflux and stir at 65°C for 20h, then filter the reaction mixture to collect the precipitated product, wash the precipitated product with deionized water 3 times, then wash it with 1mol / L hydrochloric acid three times, and continue to wash it with a large amount of deionized water until it is neutral. Finally, the obtained solid is dried in a vacuum drying oven at 50°C to constant weight to obtain the target product, carboxyl functionalized graphene.

[0112] The preparation method of the surface modified layered hexagonal boron nitride nanosheets of this embodiment is as follows: 6 parts by weight of layered hexagonal boron nitride nanosheets and 100 parts by weight of anhydrous ethanol are mixed, and ultrasonic dispersion is performed for 60 minutes to obtain solution A; then 3.0 parts of 3-aminopropyltriethoxysilane are dissolved in 100 parts by weight of anhydrous ethanol, and stirred evenly to obtain solution B; solution B is slowly added dropwise to solution A, and refluxed at 80°C for 8 hours; after the reaction is completed, solid powder is collected by centrifugation, and then the solid powder is washed twice with anhydrous ethanol, and finally the wet solid powder is dried in a vacuum drying oven at 60°C for 24 hours to obtain surface modified layered hexagonal boron nitride nanosheets.

[0113] The preparation method of the surface-modified microcrystalline cellulose of this embodiment is as follows: by weight, 9 parts of microcrystalline cellulose, 6.0 parts of laurin and 100 parts of a mixed solution of ethanol and deionized water in a mass ratio of 1:1 are mixed, ultrasonicated for 20 minutes, and then stirred at 60°C for 240 minutes, and then the solution is poured into a rotary evaporator to remove the remaining water / ethanol in the solution at 75°C and 50 Torr, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain surface-modified microcrystalline cellulose.

[0114] The first adhesive resin layer or the second adhesive resin layer of this embodiment is polyethylene modified with maleic anhydride, and the maleic anhydride grafting rate is 2%.

[0115] The total thickness of the co-extruded high barrier film of this embodiment is 90 μm, wherein the thickness ratio of the first modified polyethylene layer, the first adhesive resin layer, the first polyamide composite layer, the ethylene-vinyl alcohol copolymer composite layer, the second adhesive resin layer, the second polyamide composite layer and the second modified polyethylene layer is 3:5:3:6:3:5:3. The first modified polyethylene layer and the second modified polyethylene layer are of the same material and the same preparation method with equal thickness; the first polyamide composite layer and the second modified polyamide composite layer are of the same material and the same preparation method with equal thickness; the first adhesive resin layer and the second adhesive resin layer are of the same material and the same preparation method with equal thickness.

[0116] This embodiment also provides a method for preparing a high-heat-resistant, high-strength, multi-layer co-extruded high-barrier film, comprising the following steps:

[0117] S1. Mixing raw materials: Under a nitrogen environment, the raw materials of each layer of the multi-layer co-extruded high barrier film are respectively prepared in proportion and put into a mixer for uniform mixing, and then respectively sent to an extruder for melting.

[0118] S2. Plasticizing extrusion: extrude the layers of the high barrier film in order using an extruder. The extruder temperature of the first modified polyethylene layer and the second modified polyethylene layer is 190°C; the extruder temperature of the first adhesive resin layer and the second adhesive resin layer is 205°C; the extrusion temperature of the first polyamide composite layer and the first polyamide composite layer is 300°C; the extrusion temperature of the ethylene-vinyl alcohol copolymer composite layer is 220°C.

[0119] S3. Blow molding: The multi-layer molten film material coming out of the extruder is extruded through a circular die head, and cooling air is continuously introduced into the film bubble to make the film bubble expand evenly. The blow ratio is adjusted to 3.5 to obtain the ideal film thickness uniformity and transverse orientation. The die head temperature is controlled at 250℃ to ensure that each layer of material maintains good fluidity and interlayer bonding.

[0120] S4. Cooling and shaping: Use an efficient cooling system to quickly and evenly cool the film bubble, control the cooling air temperature to 25°C, and adjust the cooling wind speed to 12m / s. Ensure that the film bubble remains stable during the cooling process to avoid wrinkles or local deformation, and fold and flatten the film bubble when it is completely cooled to room temperature.

[0121] S5. Traction and winding: Use a precisely controlled traction roller system to traction the cooled and shaped film at a stable speed. The traction speed is controlled at 50m / min and is coordinated with the extrusion speed and blow-up ratio to obtain the required longitudinal orientation and film thickness. A tension control system is used to keep the film tension at a constant level to avoid excessive stretching or relaxation. Finally, an automatic roll-changing device is used to continuously wind up the formed multi-layer co-extruded high-barrier film. The winding tension is controlled at 1.5N / cm to ensure that the roll structure is tight and uniform without bubbles and wrinkles.

[0122] Comparative Example 1

[0123] It is basically the same as Example 1, except that carboxyl functionalized graphene is not added to the first modified polyethylene layer and the second modified polyethylene layer for preparing the high barrier film.

[0124] Comparative Example 2

[0125] The method is basically the same as Example 1, except that the surface-modified layered hexagonal boron nitride nanosheets are not added to the first polyamide composite layer and the second polyamide composite layer in preparing the high barrier film.

[0126] Comparative Example 3

[0127] The method is basically the same as Example 1, except that surface-modified microcrystalline cellulose is not added in the preparation of the ethylene-vinyl alcohol copolymer composite layer of the high barrier film.

[0128] Performance Testing:

[0129] Puncture resistance test: Conducted in accordance with ASTM D1709-04. This test simulates the impact of sharp objects on packaging materials and evaluates the material's ability to resist penetration. High puncture resistance means that the packaging can better protect the contents from external mechanical damage and improve the safety of the product during transportation and storage. This performance is particularly important for the packaging of delicate or fragile items that need protection.

[0130] Water vapor permeability test: Follow GB 1037 "Test method for water vapor permeability of plastic film and sheet - cup method" standard, use W3 / 031 water vapor transmission rate tester for 24 hours. This index reflects the ability of the material to block water vapor, which is crucial for keeping the contents of the package dry and preventing moisture from invading. Good moisture permeability barrier performance can effectively extend the shelf life of moisture-sensitive products such as food and medicine, and maintain product quality.

[0131] Gas permeability test: GB 1038 "Plastic film and sheet gas permeability test method - differential pressure method" standard was used, and the Classic2016 differential pressure gas permeameter was used to conduct a 24-hour oxygen permeability test, with a test pressure of 0.1MPa. This test evaluates the material's oxygen barrier performance, which is of great significance for preventing food from oxidative deterioration, extending the shelf life, and protecting oxygen-sensitive medicines and electronic components. Excellent oxygen barrier performance can significantly improve the protective effect of packaging.

[0132] The high temperature resistance test is evaluated by comparing the tensile strength after heat treatment at room temperature (20°C) and 90°C, and calculating the tensile strength retention rate, strength retention rate = (tensile strength after heat treatment / tensile strength at room temperature) × 100%. Specifically, the sample is heat treated at 90°C for 2 hours and then cooled to room temperature for testing. This test reflects the ability of the material to maintain mechanical properties in a high temperature environment. The choice of heat treatment time (2 hours) is intended to simulate the long-term high temperature exposure that may be encountered in actual applications. High temperature resistance ensures that the packaging maintains integrity and stability under various temperature conditions, which is particularly important for packaging materials that require heat treatment or are used in high temperature environments, such as microwave-heated food packaging, hot-filled containers, or product packaging stored in high temperature environments. Excellent high temperature resistance not only increases the scope of application of packaging materials, but also enhances their reliability and safety under extreme conditions.

[0133] Heat shrinkage: The heat shrinkage test is carried out in accordance with ASTM D1204, and the test condition is 150℃ for 30 minutes. This test evaluates the important index of dimensional stability of materials in high temperature environment. Specifically, the samples are cut into standard sizes, reference lines are marked on their surfaces, and then placed in an oven at 150℃ for 30 minutes. After cooling to room temperature, the dimensional changes of the samples in the machine direction and transverse direction are measured, and the heat shrinkage is calculated. This test simulates the extreme conditions that packaging materials may encounter in high temperature environments, such as hot filling processes or high temperature storage environments. Low heat shrinkage means that the material can maintain its shape and dimensional stability at high temperatures, which is essential for maintaining the integrity of the packaging, preventing deformation and ensuring sealing. Excellent thermal stability not only improves the reliability of the packaging, but also expands its use in high temperature applications, such as hot filling food packaging, medical device sterilization packaging, etc. In addition, good dimensional stability also helps to maintain printing quality and packaging appearance, ensuring that the product maintains good visual effects and brand recognition throughout its life cycle.

[0134] The properties of the high barrier films of Examples 1 to 4 and Comparative Examples 1 to 3 are summarized in Table 2.

[0135] Table 2 Performance summary of high barrier films of Examples 1 to 4 and Comparative Examples 1 to 3

[0136]

[0137] The main difference between Comparative Example 1 and Example 1 is that carboxyl-functionalized graphene is not added to the first modified polyethylene layer and the second modified polyethylene layer for preparing the high barrier film. As can be seen from Table 2, the addition of carboxyl-functionalized graphene can significantly improve the puncture resistance, oxygen barrier properties, water vapor barrier properties, high temperature strength retention rate, and reduce thermal shrinkage. This is because carboxyl-functionalized graphene has excellent mechanical strength and barrier properties, and its sheet structure forms a circuitous path in the polyethylene matrix, effectively blocking the penetration of gas and water vapor molecules. At the same time, the strong interaction between carboxyl-functionalized graphene and the polyethylene matrix enhances the overall mechanical properties and thermal stability of the material, thereby improving the puncture resistance and high temperature resistance, and reducing thermal shrinkage.

[0138] The main difference between Comparative Example 2 and Example 1 is that the first polyamide composite layer and the second polyamide composite layer for preparing the high barrier film do not add surface-modified layered hexagonal boron nitride nanosheets. As can be seen from Table 2, the addition of surface-modified layered hexagonal boron nitride nanosheets can further improve the barrier properties and high temperature resistance of the material, and significantly reduce the thermal shrinkage rate. This is because the surface-modified layered hexagonal boron nitride nanosheets have excellent thermal conductivity and barrier properties, and they are uniformly dispersed in the polyamide matrix to form an effective barrier network. At the same time, its surface modification improves the compatibility with the matrix and enhances the interfacial bonding force, thereby improving the overall performance of the material. In particular, the high thermal stability of hexagonal boron nitride significantly improves the high temperature resistance and dimensional stability of the material.

[0139] The main difference between Comparative Example 3 and Example 1 is that surface-modified microcrystalline cellulose is not added to the ethylene-vinyl alcohol copolymer composite layer for preparing the high-barrier film. As can be seen from Table 2, the addition of surface-modified microcrystalline cellulose can improve the mechanical strength, barrier properties and thermal stability of the material. This is because the surface-modified microcrystalline cellulose has a high degree of crystallinity and a high specific surface area, forming a reinforced network structure in the ethylene-vinyl alcohol copolymer matrix. Its surface modification enhances the compatibility and interfacial bonding with the matrix, effectively improving the puncture resistance of the material. At the same time, the presence of microcrystalline cellulose increases the diffusion path of gas and water vapor molecules, improving the barrier properties. In addition, the high thermal stability of microcrystalline cellulose and its strong interaction with the matrix also improve the high temperature resistance and dimensional stability of the material.

[0140] In general, the present invention achieves a synergistic enhancement effect of performance in a multilayer co-extruded high-barrier film by rationally combining carboxyl functionalized graphene, surface-modified layered hexagonal boron nitride nanosheets and surface-modified microcrystalline cellulose. This composite strategy significantly improves the mechanical strength, barrier properties, high temperature resistance and dimensional stability of the material, making the high-barrier film superior to the control samples with or without these functional fillers added in all performance indicators. This multi-component, multi-layer structure design provides new ideas and possibilities for the development of high-performance packaging materials.

[0141] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A high heat-resistant, high-strength, multi-layer co-extruded high-barrier film, characterized in that: The invention comprises seven mutually contacting films, which are, in order, a first modified polyethylene layer, a first adhesive resin layer, a first polyamide composite layer, an ethylene-vinyl alcohol copolymer composite layer, a second adhesive resin layer, a second polyamide composite layer and a second modified polyethylene layer; The first modified polyethylene layer or the second modified polyethylene layer is prepared from the following components by weight: 2 parts of carboxyl functionalized graphene, 0.8-1.5 parts of epoxidized soybean oil, 40-60 parts of carboxyl functionalized polyethylene and 0.5-1 part of sodium dodecylbenzene sulfonate; The first polyamide composite layer or the second polyamide composite layer is prepared from the following components by weight: 3.0-6.0 parts of surface-modified layered hexagonal boron nitride nanosheets, 0.3-0.6 parts of erucic acid amide and 60-80 parts of polyamide mixed powder; The ethylene-vinyl alcohol copolymer composite layer is prepared from the following components by weight: 100 parts of ethylene-vinyl alcohol copolymer, 2.0-4.5 parts of surface-modified microcrystalline cellulose and 0.3-0.8 parts of polyethylene wax; The mass ratio of the carboxyl functionalized graphene to the carboxyl functionalized polyethylene is 1:(20-30); The preparation method of the carboxyl functionalized polyethylene is as follows: 100 parts of mixed polyethylene, 300-500 parts of xylene and 0.1-0.5 parts of diisopropylbenzene peroxide are mixed uniformly by weight, and then 5-15 parts of acrylic acid are added, and the mixture is heated to 120-150° C. under a nitrogen atmosphere, and then stirred for reaction for 120-240 minutes. After the reaction is completed, the cooled reaction solution is slowly injected into 200 parts of methanol in a dropwise manner, and the target product can be observed to precipitate in the form of white flocculent, and then the obtained precipitated product is collected by vacuum filtration separation technology, and the precipitated product is washed 3 times with methanol, and finally, the wet precipitated product is placed in a vacuum drying device, and dried at 50-60° C. for 12-24 hours to constant weight, so as to obtain the desired carboxyl functionalized polyethylene; The mixed polyethylene is composed of low-density polyethylene and linear low-density polyethylene in a mass ratio of (4-6):(6-4); The preparation method of the carboxyl functionalized graphene is as follows: first, 5 to 10 parts of graphene oxide are added to 200 parts of deionized water at 150 °C. W power for 120-240 min to form a colloidal dispersion, then, 40 parts of hydrazine hydrate are slowly added to the dispersion, the reaction mixture is stirred under reflux conditions for 6-12 h, and then the precipitated product is collected by filtration, and then the precipitated product is washed with deionized water for 3 times, and then dried in a vacuum drying oven at 50-65 ° C to constant weight to obtain chemically reduced graphene oxide; next, 6-12 parts of chemically reduced graphene oxide and 200 parts of toluene are mixed evenly, and then 20-28 parts of azobisisobutyronitrile are added, and vigorously stirred at 70-80 ° C for 240 min under an argon atmosphere, and then the solution is cooled to room temperature and the solution is filtered to collect the precipitate, and the precipitate is washed with toluene 3 times, and then the wet precipitated product is placed in a vacuum drying device to obtain cyano-modified chemically reduced graphene oxide at room temperature to constant weight; then, 10-16 parts of cyano-modified chemically reduced graphene oxide are dispersed in 100 parts of methanol, and 100 parts of 10 mol / L sodium hydroxide aqueous solution, reflux and stir at 55-65°C for 10-20h, then filter the reaction mixture to collect the precipitated product, wash the precipitated product with deionized water for 3 times, then wash it with 1mol / L hydrochloric acid for 3 times, continue to wash with a large amount of deionized water until neutral, finally, dry the obtained solid in a vacuum drying oven at 50°C to constant weight, and the target product, carboxyl functionalized graphene, can be obtained; The preparation method of the surface modified layered hexagonal boron nitride nanosheets is as follows: by weight, 2 to 6 parts of layered hexagonal boron nitride nanosheets and 50 to 100 parts of anhydrous ethanol are mixed, and ultrasonic dispersion is performed for 30 to 60 minutes to obtain a solution A; then 1.0 to 3.0 parts of 3-aminopropyltriethoxysilane are dissolved in 50 to 100 parts of anhydrous ethanol, and stirred evenly to obtain a solution B; solution B is slowly added dropwise to solution A, and refluxed at 60 to 80° C. for 4 to 8 hours; after the reaction is completed, solid powder is collected by centrifugation, and then the solid powder is washed twice with anhydrous ethanol, and finally the wet solid powder is dried in a vacuum drying oven at 40 to 60° C. for 12 to 24 hours to obtain a surface modified layered hexagonal boron nitride nanosheet; The preparation method of the surface-modified microcrystalline cellulose is as follows: by weight, 4 to 9 parts of microcrystalline cellulose, 3.0 to 6.0 parts of lauric acid glyceride and 100 parts of a mixed solution of ethanol and deionized water in a mass ratio of 1:1 are mixed, and then ultrasonicated for 10 to 20 minutes, and then stirred at 40 to 60° C. for 120 to 240 minutes, and then the solution is poured into a rotary evaporator to remove the remaining water / ethanol in the solution at 65 to 75° C. and 50 Torr, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain the surface-modified microcrystalline cellulose.

2. A high heat-resistant, high-strength, multi-layer co-extruded high-barrier film according to claim 1, characterized in that: The first adhesive resin layer or the second adhesive resin layer is polyethylene modified by maleic anhydride, and the maleic anhydride grafting rate is 0.5% to 2%.

3. A high heat-resistant, high-strength, multi-layer co-extruded high-barrier film according to claim 1, characterized in that: The total thickness of the co-extruded high barrier film is 30-90 μm, wherein the thickness ratio of the first modified polyethylene layer, the first adhesive resin layer, the first polyamide composite layer, the ethylene-vinyl alcohol copolymer composite layer, the second adhesive resin layer, the second polyamide composite layer and the second modified polyethylene layer is 3:5:3:6:3:5:3; The first modified polyethylene layer and the second modified polyethylene layer are of the same material and prepared in the same method with equal thickness; the first polyamide composite layer and the second modified polyamide composite layer are of the same material and prepared in the same method with equal thickness; the first adhesive resin layer and the second adhesive resin layer are of the same material and prepared in the same method with equal thickness.

4. A method for preparing a high heat-resistant, high-strength, multi-layer co-extruded high-barrier film as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Mixing raw materials: Under a nitrogen environment, the raw materials of each layer of the multi-layer co-extruded high barrier film are respectively prepared in proportion and put into a mixer for uniform mixing, and then respectively sent to an extruder for melting; S2. Plasticizing extrusion: in the order of the layers of the high barrier film, the layers are co-extruded by an extruder, the extruder temperature of the first modified polyethylene layer and the second modified polyethylene layer is 182-190°C; the extruder temperature of the first adhesive resin layer and the second adhesive resin layer is 190-205°C; the extrusion temperature of the first polyamide composite layer and the first polyamide composite layer is 280-300°C; the extrusion temperature of the ethylene-vinyl alcohol copolymer composite layer is 200-220°C; S3. Blow molding: The multi-layer molten film material from the extruder is extruded through the annular die head, and cooling air is continuously introduced into the film bubble to make the film bubble expand evenly. The blow ratio is adjusted to 2.5~3.5 to obtain the ideal film thickness uniformity and transverse orientation. The die head temperature is controlled to 230~250℃ to ensure that each layer of material maintains good fluidity and interlayer bonding; S4. Cooling and shaping: Use an efficient cooling system to quickly and evenly cool the film bubble, control the cooling air temperature to 15-25°C, and adjust the cooling wind speed to 8-12m / s to ensure that the film bubble remains stable during the cooling process to avoid wrinkles or local deformation. Fold and flatten the film bubble when it is completely cooled to room temperature; S5. Traction and winding: Use a precisely controlled traction roller system to traction the cooled and shaped film at a stable speed. The traction speed is controlled at 30~50m / min and is coordinated with the extrusion speed and blowing ratio to obtain the required longitudinal orientation and film thickness. A tension control system is used to keep the film tension at a constant level to avoid excessive stretching or relaxation. Finally, an automatic roll changing device is used to continuously wind up the formed multi-layer co-extruded high barrier film. The winding tension is controlled at 0.5~1.5N / cm to ensure that the roll structure is tight and uniform without bubbles and wrinkles.

5. Use of a high heat-resistant, high-strength, multi-layer co-extruded high-barrier film as claimed in any one of claims 1 to 3 or a high heat-resistant, high-strength, multi-layer co-extruded high-barrier film prepared by the preparation method as claimed in claim 4 in food packaging, electronic device packaging, pharmaceutical packaging and new energy battery packaging.

Citation Information

Patent Citations

  • Method for preparing high-blocking polyethylene film

    CN105778208A

  • Controllable method for synthesizing carboxylic graphene oxide and prepared nano material

    CN102433032A

  • Seven-layer co-extrusion transparent high-isolation film and preparation method thereof

    CN102700210A

  • Preparation method of functionalized graphene-polyethylene composite film

    CN106947143A

  • Wear resistant and antistatic polyamide composite material and preparation method thereof

    CN106967293A